Karakteristik perkembangan anak madrasah ibtidaiyah dalam perspektif psikologi pendidikan - Prihandini, Ardiana silvi (Maliki Interdisciplinary Journal, 2026)
This study aims to describe the developmental characteristics of Madrasah Ibtidaiyah (MI) students from the perspective of educational psychology and to identify the factors that influence these developments. The research focuses on four main developmental aspects: cognitive, social, emotional, and moral-spiritual. A literature review method was used, with data sources gathered from journals, educational psychology books, and relevant previous studies. The findings indicate that children at the Madrasah Ibtidaiyah (MI) level are in the concrete operational stage, meaning their thinking processes are logical but still dependent on real-life experiences. Social interaction begins to develop more broadly through relationships with peers and teachers, and cooperative behavior becomes more visible. Emotional regulation improves, although some children still require guidance in expressing and controlling emotions appropriately. The moral and spiritual aspects become a distinctive developmental feature in Madrasah Ibtidaiyah (MI) students due to the implementation of religious values and character-building practices in both school and family environments. Children's development is influenced by internal factors such as motivation and biological conditions, as well as external factors including parenting style, school environment, media exposure, and cultural background. The results of this study are expected to provide meaningful insights for teachers and parents in implementing educational strategies that align with the developmental needs of children.